Does lowering and narrowing the inflation target band enhance the effectiveness of monetary policy transmission? Evidence from South Africa - Ndou, Eliphas (Asian Journal of Economic Modelling, 2026)
The South African Reserve Bank has indicated since 2024 the urgency to lower the current inflation target (IT) band from 3-6% to a lower target point. This paper estimates the impact of various IT bands on the interest rate pass-through and the mark-up of repo rate changes to weighted lending rates in South Africa. It examines whether the interest rate pass-through to lending rates differs when inflation is within three ranges: (i) 0-3%, (ii) 3-6%, or (iii) above 6%. The findings suggest that the pass-through is higher and the mark-up is lower when inflation is between 0-3% compared to within the 3-6% band. Additionally, the paper explores the effects of narrowing the target band from 3-6% to 2-4%. Evidence indicates that narrowing the target band from 3-6% to 2-4% results in a higher interest rate pass-through to lending rates. These findings imply that the transmission of monetary policy is more effective when inflation is within the 2-4% range. Consequently, the SARB’s adoption of a lower inflation target will enhance the transmission of policy rate changes to lending rates and reduce the mark-up.